2012
DOI: 10.1371/journal.pone.0034072
|View full text |Cite
|
Sign up to set email alerts
|

Swim-Training Changes the Spatio-Temporal Dynamics of Skeletogenesis in Zebrafish Larvae (Danio rerio)

Abstract: Fish larvae experience many environmental challenges during development such as variation in water velocity, food availability and predation. The rapid development of structures involved in feeding, respiration and swimming increases the chance of survival. It has been hypothesized that mechanical loading induced by muscle forces plays a role in prioritizing the development of these structures. Mechanical loading by muscle forces has been shown to affect larval and embryonic bone development in vertebrates, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 42 publications
2
91
1
3
Order By: Relevance
“…In both cases, the most responsive elements are the latter formed peripheral elements in the dorsal and anal fins, and the neural and haemal elements of preural centra in the caudal fin. Similar lines of evidence were recently reported Young and Badyaev, 2010;Fiaz et al, 2012) indicating that the latter formed elements in developing endoskeleton have a greater susceptibility to display plastic response with regards to changes in environmental conditions (or epigenetic factors). By analyzing the mechanical load exerted through muscle stimulation on the developing bony foraging apparatus of shrews (Sorex monticolus), Young and Badyaev (2010) found that the size and shape of the mandible is strongly influenced in late, but not in early, ossifying regions of the bone.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In both cases, the most responsive elements are the latter formed peripheral elements in the dorsal and anal fins, and the neural and haemal elements of preural centra in the caudal fin. Similar lines of evidence were recently reported Young and Badyaev, 2010;Fiaz et al, 2012) indicating that the latter formed elements in developing endoskeleton have a greater susceptibility to display plastic response with regards to changes in environmental conditions (or epigenetic factors). By analyzing the mechanical load exerted through muscle stimulation on the developing bony foraging apparatus of shrews (Sorex monticolus), Young and Badyaev (2010) found that the size and shape of the mandible is strongly influenced in late, but not in early, ossifying regions of the bone.…”
Section: Discussionsupporting
confidence: 84%
“…Zebrafish (Danio rerio) larvae subjected to swimming exercise showed an acceleration of ossification for the caudal fin elements; the ossification of hypurals and lepidotrichia occurs 15 days post-fertilization earlier in trained fish than in control fishes (Unpublished thesis). In two recent studies, it has been shown that exercise training changes the timing of formation of cartilages and bones in fishes Fiaz et al, 2012). By using different specimens and treatments, Cloutier et al (2010) have shown changes in the timing of ossification in specimens of S. alpinus reared at lower water velocities (i.e., slow velocity ¼ 0.38 cm s -1 and fast velocity ¼ 0.51 cm s -1 ) than tested in the present study.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…Modeling therefore results in a net increase or loss of bone material, and is thus important in bone development, bone growth and bone adaptation to changing loads. 4,6,40 Many studies have concluded that fish bone responds to increased loading by the process of modeling; however, most of these were conducted using fish with cellular bones (for example, Deschamps et al, 41 Eissa et al, 42 Fiaz et al 43 and Totland et al 44 ). The few studies that have focused on acellularboned fishes have provided somewhat secondary evidence for modeling.…”
Section: Modeling: Evidence For and Implications In Acellular Bonementioning
confidence: 99%